Smart metering system data analytics platform using multicore edge computing - Juan C. Olivares-Rojas; Enrique Reyes-Archundia; José A. Gutiérrez-Gnecchi; Ismael Molina-Moreno; Adriana C. Téllez-Anguiano; Jaime Cerda-Jacobo (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
The smart grid revolution has only been possible, thanks to the development and proliferation of smart meters. The increasingly growing computing capabilities for Internet of Things devices have made it possible for data to be processed directly from the devices where it is produced; this has been called edge computing. Edge computing is allowing the smart grid to become increasingly intelligent to solve problems that make electricity consumption more efficient and environmentally friendly. This work presents the implementation of a smart metering system that allows data analytics using a multiprocessing architecture directly on the smart meter. The results show that the development of smart meters with data analytics capabilities at the edge is a reality today, and the use of multiprocessing permits the improvement of data processing.